DESIGN OF LENDING SYSTEM AND RETURN OF MEDICAL RECORDS HOSPITALIZATION AT AIR FORCE HOSPITAL DR.M SALAMUN - Khofif Salnilatipa; Astia Nurul Kusgianti (Informatika, Universitas Jenderal Soedirman, 2022)
The system of borrowing and returning medical records is an important activity in the medical record unit in supporting hospital services, an important part of a hospital is the medical record section. The purpose of this study is to design a program application for a computerized loan and return of hospitalization medical records that can facilitate officers at RsAU Dr.M Salamun, lending and return systems at RSAU Dr.M Salamun there are still some obstacles that occur, where the system is still recorded in the eskpedisi book, does not use tracer in taking medical record files and using Microsoft Excel software. The purpose of this study is to create and design applications for a computerized lending and return of inpatient medical records that can facilitate medical record officers at RSAU Dr.M Salamun. The research method used is a descriptive qualitative method that includes interviews, data collection, and documentation. The method used uses the waterfall method with stages of obstacle analysis, needs analysis, system design design, program coding and program testing. The design of this system using Flowmap, Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD) was then implemented in a programming language using Microsoft Visual Basic 2010. The result of this study is the application of lending information systems and electronic or computerized return of medical records. The conclusion of this study to develop a loan and return system to minimize loss, duplicate medical records, facilitate officers, know the last track record of borrowing medical records, and know when medical records are returned by internal or external parties.